2022
DOI: 10.3390/jcm11092350
|View full text |Cite
|
Sign up to set email alerts
|

Trends of Dietary Intakes and Metabolic Diseases in Japanese Adults: Assessment of National Health Promotion Policy and National Health and Nutrition Survey 1995–2019

Abstract: Health Japan 21 is Japan’s premier health promotion policy encompassing preventive community health measures for lifestyle-related diseases. In this repeated cross-sectional survey, we report 24-year trends of type 2 diabetes mellitus (T2DM), obesity, hypertension, and their association with dietary intakes to evaluate Health Japan 21’s impact and identify gaps for future policy implementation. We analyzed data from 217,519 and 232,821 adults participating in the physical examination and dietary intake assessm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 53 publications
(66 reference statements)
2
10
0
Order By: Relevance
“… 4 Overall, these countries have made favorable changes, featured by increased consumption of fruits and vegetables as well as decreased intakes of salt and unhealthy fat. 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 These were also supported by the risk ranking between 1990 and 2019 based on the GBD data ( Table 2 , Supplementary Table S5 , and Fig. 2 ).…”
Section: Resultssupporting
confidence: 54%
“… 4 Overall, these countries have made favorable changes, featured by increased consumption of fruits and vegetables as well as decreased intakes of salt and unhealthy fat. 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 These were also supported by the risk ranking between 1990 and 2019 based on the GBD data ( Table 2 , Supplementary Table S5 , and Fig. 2 ).…”
Section: Resultssupporting
confidence: 54%
“…Regarding trends in metabolic diseases and dietary nutrition in Japan, Fauzi et al ( 6 ) recently reported, based on the NHNS data, a shift to a Western-style Japanese diet over 24 years from 1995 to 2019 and an increase in T2DM and obese/overweight individuals among men. Komeda reported that the NAFLD incidence in the Kyoto area of Japan increased from 12.9% to 34.7% between 1994 and 2004 ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the relationship between NAFLD and dietary nutrition, an excessive caloric intake, a Western-style diet, a diet high in saturated fat, and a high fructose intake have been reported as risk factors ( 5 ). Recently, Fauzi et al ( 6 ) reported trends in metabolic diseases and dietary intake in Japan over the past 24 years and found that diets have rapidly become westernized, and prevalence of obesity, overweight, and type 2 diabetes mellitus (T2DM) have increased, especially in men. However, there are no reports on the association between NAFLD and the dietary nutrient intake following the implementation of SHCs.…”
Section: Introductionmentioning
confidence: 99%
“…Based on data collected via the National Health and Nutrition Survey, mean body mass index (BMI) has significantly increased over the past two decades in Japan, and the prevalence of both type 2 diabetes (T2D) and obesity has steadily increased within the same time frame, particularly among males [ 1 ]. In Japan and other East Asian countries, patients with T2D have a lower mean BMI than patients from non-East Asian countries and a higher percentage of body fat, particularly visceral body fat, at any given BMI [ 2 ].…”
Section: Introductionmentioning
confidence: 99%